'Reasonable' perceptions of stalking: The influence of conduct severity and the perpetrator target relationship - Scott, A.; Sheridan, Lorraine (2011)
Ex-partner stalkers are more persistent and dangerous than stranger stalkers, but are less likely to be convicted of an offence. This research considerswhether the just world hypothesis (JWH) can account for this apparent contradiction. An experimental 3×3 independent factorial design was used to investigate the influence of conduct severity and the perpetrator-target relationship on perceptions of stalking. Three hundred and thirty-four students were presented with one of nine vignettes and asked to complete five scale items relating to the situation described. Conduct severity and the perpetrator-target relationship produced significant main effects for the combined scale items. The perpetrator's behaviour was perceived to constitute stalking, necessitate police intervention and/or criminal charges, and cause the target alarm or personal distress to a greater extent when the perpetrator and target were depicted as strangers rather than ex-partners. Conversely, the target was perceived to be less responsible for encouraging the perpetrator's behaviour in the stranger condition compared to the expartner condition. The JWH provides a possible explanation for the influence of the perpetrator-target relationship on perceptions of stalking. Future research could utilize more realistic vignettes to increase the impact of the perpetrator's behaviour. © 2011 Taylor & Francis.